“I’d give anything to come home”: The Farmerette Movement in Ontario during the First World War - Kechnie, Margaret (Ontario History)

(untitled) (The Ontario Historical Society, 2021)
The story of Canadian women’s involvement in the First World War is gradually emerging, little attention has been paid to the contribution of women who worked in rural Ontario during the war. This paper will deal with a little-known group of undergraduate women from the University of Toronto who supported the Canadian war effort by responding to a call for agricultural workers, particularly fruit harvesters. These workers became popularly known as “farmerettes.”